Role of Cocoa Clones and Endophyte Fungi in controlling VSD Disease in the Field - Muhammad Taufik; Asniah Asniah; Muhammad Botek; Rahayu M; Arifin Tasrif (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2021)
The fungus Ceratobasidium theobromae is the cause of vascular streak dieback (VSD) in cocoa. VSD disease can cause death in susceptible clones by more than 59%. The use of resistant cocoa clones and endophytic fungi can be an alternative for VSD disease control. The research objective was to evaluate cocoa clones and endophytic fungi to control VSD in the field. The experimental design used was a randomized block design with a factorial pattern. The first factor was cocoa clones, which consisted of clones 45 (K1) and 25 (K2), and the second factor was several types of endophytic fungi. The results showed an interaction between cacao clones and endophytic fungi isolates on the height and number of cocoa leaves. The two cacao clones tested could be naturally infected by C. theobromae without endophytic fungi, with disease incidence of VSD 5, 21% in K1, and 5.75% in K2. The two cocoa clones treated with endophytic fungi, i.e., Paecilomyces sp. EP1, Paecilomyces sp. EP2 and Paecilomyces sp. EP1 + Trichoderma sp.) did not show symptoms of VSD until 20 weeks after planting.